MOBILE LEARNING: AN EFFECTIVE LEARNING APPROACH FOR DISTANCE LEARNER - Jamaluddin, Norhafiza; Yin Yin, Khoo; Zakariya, Zainizam (Management Research Journal, 2014)
This conceptual paper attempts to provide an understanding of the effectiveness of mobile learning. Approach in distance education of mobile learning can enhance students’ interest and motivation. It also helps the adult part time students to communicate with the instructor quickly. The implementation of the mobile learning allows students to access educational information at anytime and anywhere.